Pengaruh Persepsi Manfaat, Persepsi Kemudahan, Persepsi Kepercayaan, dan Norma Subjektif terhadap MInat Menggunakan Sistem Informasi Pembayaran Elektronik (E-Payment) - Ulansari, Luh Putu Eka; Yudantara, I Gede Agus Pertama (Universitas Pendidikan Ganesha, 2021)
The study aims to determine the effect of perceived usefulness, perceived ease of use, perceived of trust and subjective norms on the interest in using electronic payment information systems (e-payment). The data collection method used a questionnaire obtained 195 respondents. The data were processed using SPSS version 22. The results of the study found that perceived benefits, perceived convenience, perceived beliefs and subjective norms had a positive effect on the interest in using electronic payment information systems (e-payment). This means that the desire of the Undiksha Faculty Academic community is influenced by its usefulness, usefulness, reliability and other parties recommending an electronic payment information system (e-payment).